2020
DOI: 10.1038/s41374-019-0326-6
|View full text |Cite
|
Sign up to set email alerts
|

Isoform-specific promotion of breast cancer tumorigenicity by TBX3 involves induction of angiogenesis

Abstract: TBX3 is a member of the highly conserved family of T-box transcription factors involved in embryogenesis, organogenesis and tumor progression. While the functional role of TBX3 in tumorigenesis has been widely studied, less is known about the specific functions of the different isoforms (TBX3iso1 and TBX3iso2) which differ in their DNA-binding domain. We therefore sought to investigate the functional consequence of this highly conserved splice event as it relates to TBX3-induced tumorigenesis. By utilizing a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…Most of them (eight out of ten) displayed a switching to a differentiated cell-like AS pattern upon Zfp207 knockdown, indicating that ZFP207 regulates an AS signature that controls pluripotency. In addition, several of the stem cell switches that we identified, such as Nasp or Tbx3, have been shown to be involved in cancer (Alekseev et al, 2011;Krstic et al, 2020).…”
Section: Discussionmentioning
confidence: 91%
“…Most of them (eight out of ten) displayed a switching to a differentiated cell-like AS pattern upon Zfp207 knockdown, indicating that ZFP207 regulates an AS signature that controls pluripotency. In addition, several of the stem cell switches that we identified, such as Nasp or Tbx3, have been shown to be involved in cancer (Alekseev et al, 2011;Krstic et al, 2020).…”
Section: Discussionmentioning
confidence: 91%
“…SPP1 also upregulates the expression of interferon-γ and interleukin-12, and is involved in Th1-mediated immunity [35,36]. Many studies revealed that SPP1 is involved in angiogenesis in tumors like breast cancer, lung cancer, melanoma and colon cancer [26,27,[37][38][39]. Despite the lack of mechanistic research, SPP1 has been highly associated with GBM angiogenesis using IHC, which consolidated our initial conclusion [40,41].…”
Section: Discussionmentioning
confidence: 73%
“…TFs in common between old heterochronic and young unpaired ECs that reflect RJV included essential regulators of EC function such as Tbx3 (refs. 61 , 62 ) and Foxo4 (ref. 63 ), a member of the FOXO family of TFs that are components of a fundamental aging regulatory pathway , Patz1 , which has been implicated in regulating p53 levels and senescence in ECs 64 , and Arnt , which participates in aryl hydrocarbon receptor signaling and is involved in several aspects of vascular biology 65 (Fig.…”
Section: Resultsmentioning
confidence: 99%